A comparative study of effect of deviated nasal septum on nasal mucociliary clearance and to comprehend the effect of septal and turbinate surgeries on restoring the mucociliary clearance - B. C. Chandra, Smitha; Bylappa, Kiran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: One of the important functions of nose is mucociliary transport by its epithelium. Any structural abnormalities of nose like deviated nasal septum, turbinate hypertrophy and polyps can easily damage the mucociliary clearance. This can lead to increased inflammation leading to osteomeatal complex obstruction and sinusitis. The purpose of the study is to determine the nasal mucociliary clearance time (NMC) in patients with deviated nasal septum. And to compare the changes in nasal mucociliary clearance time before and after septoplasty and septoplasty with turbinectomy. Methods: Nasal mucociliary clearance time was measured preoperatively in patients with deviated nasal septum on concave and convex side. Post operatively it was again recorded after septoplasty in group A and septoplasty with turbinectomy in group B. These values were compared with the control group C. Results: Postoperatively group A patients NMC time was 11.11±2.76 on convex side, 14.01±2.39 on concave side. In group B patients NMC time was 11.18±1.91 on convex side and 12.62±1.42 on concave side. Conclusions: Nasal septal deviation and hypertrophied inferior turbinates can cause considerable impairment of nasal mucociliary clearance. Septoplasty combined with partial inferior turbinectomy of compensatory hypertrophied inferior turbinate on concave side preserves the normal NMC mechanism on both the sides of nasal cavity than just septoplasty.